Study and analysis of the correlation between lumbar spondylolisthesis and Modic changes - Li, Guang-qing; Kang, Xiao; Li, Wei; Pei, Shi-shen (Frontiers in Surgery, 2024)
Background: To explore the risk factors of Modic changes in lumbar spondylolisthesis. Methods: To observe and analyze the distribution of Modic changes in different types of lumbar spondylolisthesis, degree of spondylolisthesis and degree of intervertebral disc degeneration in patients with lumbar spondylolisthesis.Statistical analysis of whether intervertebral disc degeneration and local mechanical changes,etc.,affect the occurrence of Modic changes.To further illustrate the risk factors of Modic changes in lumbar spondylolisthesis.The age in the lumbar spondylolisthesis with Modic changes group was younger than that in the lumbar spondylolisthesis without Modic changes group, and its bone mineral density(BMD) was better than that in the lumbar spondylolisthesis without Modic changes group, P<0.05.The two groups were statistically different in intervertebral disc height(IDH) and disc angle on magnetic resonance imaging(MRI).In the classification of Modic changes, the incidence of type II was the highest.The incidence of Modic changes is higher in isthmic spondylolisthesis than in degenerative spondylolisthesis.With the aggravation of lumbar spondylolisthesis and intervertebral disc degeneration, the incidence of Modic changes gradually increased.Modic changes are most commonly seen in both the upper and lower endplates.Logistic regression analysis showed that the occurrence of Modic changes in lumbar spondylolisthesis was significantly correlated with IDH,disc angle on MRI(MDA), type of spondylolisthesis, degree of spondylolisthesis and intervertebral disc degeneration, P < 0.05. Conclusions: The occurrence of Modic changes is related to the type of spondylolisthesis, the degree of spondylolisthesis, the degree of disc degeneration, the decrease of intervertebral disc height and the local stress angulation.